What is inside the Womb? An Analysis from the Perspectives of the Quran and Science - Khandoker, Morshed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
What is inside the Womb? An Analysis from the Perspectives of the Quran and Science